Altered Arginine/Agmatine Pathway and Polyamines in Adolescents Diagnosed with Major Depressive Disorder - Yazici, Kemal Utku; Ozturk, Sukru Kaan; Yazici, Ipek Percinel; Ustundag, Bilal (Korean Coll Neuropsychopharmacology, 2024)
Objective: Major depressive disorder (MDD) is common in childhood, but its etiopathogenesis is still unclear. Published neurochemical studies mostly focus on monoaminergic system, however, the pathophysiology of MDD cannot be explained by monoamine hypothesis only, medications that have effect on monoamines cannot have effect needed in all patients. We aimed to investigate the poliamine pathway of L-arginine metabolism which is proceeding by way of agmatine in adolescents with MDD. Methods: Our study involved 45 patients with MDD (case group), and 44 healthy controls (control group) between the ages of 13-17. Sociodemographic data form, Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version-DSM-5-Turkish, Beck Depression Inventory (BDI), Spielberger's State-Trait Anxiety Inventory were applied to all subjects. All subjects were evaluated in terms of the levels of serum agmatine, putrescine, spermidine, and spermine. Results: The levels of agmatine and spermine were significantly higher and putrescine and spermidine were significantly lower in case group compared with healthy controls. There was significant negative correlation with the levels of putrescine and spermidine between BDI scores, and there was significant positive correlation between the levels of spermine and BDI scores. No correlation found between the levels of agmatine and BDI scores. Conclusion: These differences that the levels of agmatine and polyamines in the MDD group seem to be a field that worth researching. In the future, the evaluation of the arginine/polyamine metabolism in MDD with larger sample and longitudinal studies is going to capable to contribute to a better understanding of the disorder.
Keywords: KEY WORDS: Major depressive disorder; Agmatine; Putrescine; Spermidine; Spermine; Adolescent.